A biomechanical analysis of venous tissue in its normal, post-phlebitic, and genetically altered conditions - McGilvray, Kirk Cameron, author; Puttlitz, Christian M., advisor (Colorado State University. Libraries, 2009)
The incidence of vein disease is very high, affecting more than 2% of the hospitalized patients in the United States; a number that is expected to increase. Post phlebitic veins, the result of chronic deep vein thrombosis, is considered to be one of the most important venous disease pathologies. Unfortunately, little information is currently available on the biomechanical effects of thrombus resolution in the deep veins. The aim of this research was to characterize the biomechanical response of both healthy and diseased venous tissue using a murine model. It was hypothesized that biomechanical response parameters derived from healthy and diseased tissue would give insight into the resultant clinical complications observed in patients following thrombus resolution. Biomechanical analysis revealed that statistically significant deleterious changes in vein wall compliance were observed following thrombus resolution. Data also revealed that matrix metallopeptidase 9 expression has a statistically significant effect on the biomechanical response of the tissue. These results indicate that clinical complications following deep venous thrombosis manifest from significant decreases in the compliance of the vein wall. Finite element analyses were also performed. Biomechanical data served as input material parameters for modeling. Finite element modeling was used to evaluate the response of the inferior vena cava under physiologic loads. The results indicate that peak stresses are generated in the circumferential direction of loading during luminal pressurization. Decreased dilatation was observed following thrombus resolution. The data indicates that deep venous thrombosis lead to increased vein wall stress in correlation with decreased luminal distensability.
Keywords: deep vein thrombosis; strain energy; venous tissue; biomedical engineering; biomechanics